Hydrological Basis and Discipline System of Cryohydrology: From a Perspective of Cryospheric Science - Ding, Yongjian; Zhang, Shiqiang; Chen, Rensheng; Han, Tianding; Han, Haidong; Wu, Jinkui; Li, Xiangying; Zhao, Qiudong; Shangguan, Donghui; Yang, Yong; Liu, Junfeng; Wang, Shengxia; et al. (Frontiers in Earth Science, 2020)
Cryohydrology, had been referred as hydrology at low temperature, concerns snow, ice, frozen ground, and cold water. It has expanded with the development of Cryospheric Science, involving hydrological processes of various cryosphere elements systematically, and coupling them with river basin hydrological processes. However, few studies have introduced the characteristic and discipline connotation of Cryohydrology from a perspective of Cryospheric Science. Here, we reviewed the evolution of the connotation of Cryohydrology, and analyzed its hydrological basis and discipline system. There are three major conclusions. (1) Cryohydrology was developed based on traditional hydrology for a single element of cryosphere, and focused on the hydrological functions of cryosphere and its impact on water cycle and water supply to other spheres. (2) The hydrological function of Cryohydrology was summarized into water conservation, runoff recharge and hydrological regulation. In detail, the water conservation function was mainly expressed as "source" and "wet islands", the runoff recharge function was mainly as a role of water supply, and the regulation function takes effective at the intra-annual and inter-annual scales. (3) The core research issues of cryohydrology are along the mainline from research method, hydrological process, watershed function, and regional impact. The most important characteristic of Cryohydrology is frequent water phase transitions and highly variate spatial and temporal scales. The Cryohydrology aims to deepen the theoretical and cognitive levels of the mechanism and process, accurately quantify the hydrological functions of the basin, and promote understanding the ecological and environmental impacts of the cryosphere.